Aborted Sudden Cardiac Death as a Presentation of Isolated Non-Compaction Cardiomyopathy - Borges-Cancel, William; Calderón, Rafael E. (Puerto Rico Health Sciences Journal, 2011)
Left ventricular non-compaction cardiomyopathy (LVNC) is a rare disorder characterized by a thick myocardial wall with two distinct layers consisting of compacted and noncompacted myocardium. The major clinical manifestations of LVNC have been described as heart failure, cardiac arrhythmias, and cardioembolic events. In this report we present a case of a young woman with LVNC who presented with aborted sudden cardiac death. This is the second case of LVNC reported in Puerto Rico, but the first presenting with this complication. Recent advances in the field of cardiology allow the identification and diagnosis of this disease; thus, preventive and treatment strategies could be established for this potentially life-threatening condition. LVNC has to be considered in young patients presenting with sudden cardiac death.